2016
DOI: 10.1111/psyg.12161
|View full text |Cite
|
Sign up to set email alerts
|

Necker cube copying may not be appropriate as an examination of dementia: reanalysis from the Tajiri Project

Abstract: Our results suggested that Necker cube copying may evaluate visual illusion as well as visuoconstructional ability. The Necker cube may not be an appropriate test to detect participants with MCI due to dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Therefore, further analysis would be necessary to confirm that the 3 mm vertex criterion is appropriate, as their score using this criterion was six out of eight, to distinguish community-dwelling elderly from patients with cognitive impairments of dementia by comparing the characteristics assessed by the 3-vertex criterion with the results of other evaluation methods and a greater variety of participants. 22,23 All of the participants in our study demonstrated either one parallel line error or none, regardless of their age, years of education, and MoCA-J scores. Therefore, it can be said that the parallel line error is small in the elderly.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, further analysis would be necessary to confirm that the 3 mm vertex criterion is appropriate, as their score using this criterion was six out of eight, to distinguish community-dwelling elderly from patients with cognitive impairments of dementia by comparing the characteristics assessed by the 3-vertex criterion with the results of other evaluation methods and a greater variety of participants. 22,23 All of the participants in our study demonstrated either one parallel line error or none, regardless of their age, years of education, and MoCA-J scores. Therefore, it can be said that the parallel line error is small in the elderly.…”
Section: Discussionmentioning
confidence: 67%
“…If neuropsychological symptoms, such as visuo‐perceptual disability, occur as part of the dementia seen with Alzheimer's disease, 15 the number of correct vertices would be expected to be less than six using the 3 mm vertex criterion. Therefore, further analysis would be necessary to confirm that the 3 mm vertex criterion is appropriate, as their score using this criterion was six out of eight, to distinguish community‐dwelling elderly from patients with cognitive impairments of dementia by comparing the characteristics assessed by the 3‐vertex criterion with the results of other evaluation methods and a greater variety of participants 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…For the CC item, Oonuma et al [ 54 ] reported that 31.1% of individuals with normal cognition failed to complete the test correctly. The difficult level revealed for the single CC item in this study suggested that 37% (306/827) of the participants failed to complete the task.…”
Section: Discussionmentioning
confidence: 99%